Effects of Fermented Camel Milk Supplemented with Sidr Fruit (Ziziphus spina-christi L.) Pulp on Hyperglycemia in Streptozotocin-Induced Diabetic Rats - El Sayed Hassan Atwaa; Magdy Ramadan Shahein; Barakat M. Alrashdi; Moustafa A. A. Hassan; Mohamed A. Alblihed; Naief Dahran; Fatma Abo Zakaib Ali; Ehab Kotb Elmahallawy (Fermentation, 2022)
Diabetes is one of the most common chronic metabolic diseases, and its occurrence rate has increased in recent decades. Sidr (Ziziphus spina-christi L.) is a traditional herbaceous medicinal plant. In addition to its good flavor, sidr has antidiabetic, anti-inflammatory, sedative, analgesic, and hypoglycemic activities. Camel milk has a high nutritional and health value, but its salty taste remains the main drawback in relation to its organoleptic properties. The production of flavored or fortified camel milk products to mask the salty taste can be very beneficial. This study aimed to investigate the effects of sidr fruit pulp (SFP) on the functional and nutritional properties of fermented camel milk. SFP was added to camel milk at rates of 5%, 10%, and 15%, followed by the selection of the best-fermented product in terms of functional and nutritional properties (camel milk supplemented with 15% SFP), and an evaluation of its hypoglycemic activity in streptozotocin (STZ)-induced diabetic rats. Thirty-two male adult albino rats (weighing 150–185 g) were divided into four groups: Group 1, nontreated nondiabetic rats (negative control); Group 2, diabetic rats given STZ (60 mg/kg body weight; positive control); Group 3, diabetic rats fed a basal diet with fermented camel milk (10 g/day); and Group 4, diabetic rats fed a basal diet with fermented camel milk supplemented with 15% SFP (10 g/day). The results revealed that supplementation of camel milk with SFP increased its total solids, protein, ash, fiber, viscosity, phenolic content, and antioxidant activity, which was proportional to the supplementation ratio. Fermented camel milk supplemented with 15% SFP had the highest scores for sensory properties compared to other treatments. Fermented camel milk supplemented with 15% SFP showed significantly decreased (p < 0.05) blood glucose, malondialdehyde, low-density lipoprotein-cholesterol, cholesterol, triglycerides, aspartate aminotransferase, alanine aminotransferase, creatinine, and urea, and a significantly increased (p < 0.05) high-density lipoprotein-cholesterol, total protein content, and albumin compared to diabetic rats. The administration of fermented camel milk supplemented with 15% SFP in diabetic rats restored a series of histopathological changes alonsgside an improvement in various enzyme and liver function tests compared to the untreated group, indicating that fermented camel milk supplemented with 15% SFP might play a preventive role in such patients.